2017
DOI: 10.1096/fj.201700415rr
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinating enzyme USP48 stabilizes TRAF2 and reduces E‐cadherin‐mediated adherens junctions

Abstract: The tumor necrosis factor receptor-associated factor 2 (TRAF2) is a second messenger adaptor protein that plays an essential role in propagating TNF-α-mediated signaling pathways. Modulation of TRAF2 activity by ubiquitination is well studied; however, the deubiquitinating enzyme (DUB), which regulates TRAF2 stability, has not been identified. Here we reveal USP48 as the first identified DUB to deubiquitinate and stabilize TRAF2 in epithelial cells. Down-regulation of USP48 increases K48-linked polyubiquitinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 57 publications
(76 reference statements)
1
27
0
Order By: Relevance
“…Phosphorylation of TRAF2 promotes K63‐linked polyubiquitination . It is also reported that the deubiquitinating enzyme USP48 stabilizes TRAF2 by modifying its ubiquitination .…”
Section: Discussionmentioning
confidence: 95%
“…Phosphorylation of TRAF2 promotes K63‐linked polyubiquitination . It is also reported that the deubiquitinating enzyme USP48 stabilizes TRAF2 by modifying its ubiquitination .…”
Section: Discussionmentioning
confidence: 95%
“…USP48 (also known as USP31) interacted with and deubiquitinated TRAF2 in beas2B cells [71]. A noteworthy fact is that TRAF2 in JNK pathway was targeted by USP48, but not TRAF2 in NF-κB signaling [71].…”
Section: Usp48mentioning
confidence: 99%
“…Exposure to TNFα caused GSK3β-mediated phosphorylation of USP48, leading to deubiquitination of TRAF2 in beas2B cells, increasing JNK signaling upon TNF-α-induction [71].…”
Section: Usp48mentioning
confidence: 99%
“…Deubiquitination and DUBs have been shown to regulate adherence of junctional proteins [101]. For example, USP48 regulates E-cadherin mRNA levels through stabilizing the TRAF2-JNK pathway in lung epithelial cells [69]. This study exhibits an indirect effect of DUBs on regulation of E-cadherin levels and lung epithelial barrier integrity.…”
Section: Dubsmentioning
confidence: 66%